Relasi Suami Istri dalam Pengasuhan Anak Perspektif Mubadalah (Studi Kasus di Desa Rajabasa Lama II) - Ibnu Akbar Maliki; Anta Mustika Sari (Center of Gender Studies and Child of State Islamic Institute of Metro, 2023)
Children are an investment for the family as well as the next generation who need guidance from both parents. Parents have an important role in childcare. Mothers and fathers have the same obligation to educate and care for their children. But it is unfortunate that currently the awareness of a father to take part in caring for his child is very low, childcare is identical to the work required for a mother alone. Whereas a child also has rights that must be fulfilled during the care period, one of which is to get care from both parents, both mothers and fathers. This type of research is field research and is descriptive in nature. Primary data sources in this research are parents and children involved in parenting in Rajabasa Lama II Village, Labuhan Ratu District, East Lampung Regency. Secondary data sources used are books and papers that are in accordance with the discussion. Data collection techniques using semi-structured interviews and observation. The results of this study indicate that the practice of childcare carried out in Rajabasa Lama II village is more dominant to a mother, while a father who should also be involved in caring for and educating children has not carried out his obligations as stated in KHI and Law Number 1 concerning marriage. The existence of the concept of mubadalah which talks about the relationship between men and women in various matters, is associated with the position of men and women in the family, especially childcare, this is in line with the regulations conveyed in KHI and Law number 1 of 1974 shows that the importance of the role of mothers and fathers in educating and caring for children, both boys and girls by fulfilling their rights and needs. Keyword: Childcare; Partnership; Mubadalah